Repellency of Orange Peel Eco-Enzyme to Reared German Cockroaches (Blattella germanica L.) - Robby Jannatan; Resti Rahayu (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2023)
The German cockroach is a common pest worldwide that has developed insecticide resistance. Eco-enzyme with an aromatic aroma is one alternative way to prevent insecticide resistance development and repel the German cockroach population. This study aims to determine the value and level of repellency of orange peels' eco-enzyme. The method of this study is a Repellency test of four concentrations of eco-enzyme to the reared resistant German cockroach. The repellency level of eco-enzyme at low concentrations (10%) to high concentrations (100%) ranges from high repellent to very high repellent at one hour of observation. The repellency decreases until 48 hours of observation and ranges from medium to high repellent. Eco-enzyme solutions that are eco-friendly, simple to make, and low in toxicity to humans can use as an alternative to synthetic repellents.